Additives for animal feeding: The Institute of Animal Science on its 50 years - García Hernández, Yaneisy; García Curbelo, Yanelys (Cuban Journal of Agricultural Science, 2016)
This review is aimed at offering information on the main research studies developed during 50 years by the Institute of Animal Science of the Republic of Cuba on the subject of the use of additives in animal feeding. Aspects dealing with nutritional and animal additives used in monogastric and ruminant animals are also envisaged. Key words: monogastric, ruminants, nutritional additives, animal additives, animal production